PHRASEOLOGICAL UNITS WITH CONCEPT “HEN”,”ROOSTER” AND “CHICKEN” IN ENGLISH AND UZBEK LANGUAGES (Academicia Globe: Inderscience Research, 2021)
This article explores phraseological units with concepts “hen”, “rooster” and ”chicken” in English and Uzbek cultures. Differences and similarities of these expressions are determined in two unrelated languages.